Affective post-stroke disorders: pathogenesis, diagnosis, treatment - V. A. Mikhailov; A. K. Druzhinin; N. I. Shova (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2018)
Cerebral strokes in 25-90 % of cases are accompanied by the emergence of various mental disorders. Thus, in 80% of cases of mental disorders manifest mental disorders nonpsychotic level (affective, cognitive, behavioral, personality), which are dominated by depressive disorders. The maximum frequency of depressive episodes recorded in the periods 3-6 months after stroke (70%). The risk of death when combined stroke depression increases 2.6 times, and the treatment of depression can prevent 11% of stroke. National center of psychiatry and neurology im. V.M. Bekhterev has 25 years of experience of use in patients with consequences of sharp violations of cerebral circulation of the drug gliatilin, which not only improves the neuroplasticity of the brain tissue but improves cognitive function and normalization of the emotional sphere of patients. One of the most important symptoms of depression are sleep disturbances. Changes in the structure of sleep in the acute period of stroke prognostic importance. Antidepressant trazodone used in the treatment of depressive disorders accompanied by insomnia. Doctors evaluated the effectiveness of the therapy, trittico in 34% of cases as excellent, 45% as good and 21% of cases as satisfactory. Patients evaluated the effectiveness of the drug in 24% of cases as excellent, 55% as good and 22% as satisfactory. To continue the drug treatment were in agreement 87% of patients.